A preparation process of star crystal glazed ceramics

By adjusting the particle size gradient of raw material components in the star crystal glaze and using nanozirconia and other materials, the problem of difficulty in achieving shiny crystal effects in ceramic products is solved, and the wear resistance and crack resistance and aesthetics of ceramic products are improved.

CN118930326BActive Publication Date: 2025-03-21FOSHAN TAOYING NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411010663.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2025-03-21
Estimated Expiration
2044-07-26

AI Technical Summary

Technical Problem

Existing ceramic products are difficult to achieve shiny crystal effects while ensuring wear and crack resistance, and lack good permeability and three-dimensionality.

Method used

By adjusting the particle size gradient distribution of different raw material components in the star crystal glaze, the adhesion and stability of the glaze are enhanced, and combined with the use of nanozirconia, glaze slurry and suspension agents, the gloss and starlight effect of the ceramic is improved.

Benefits of technology

It has achieved the effect of ceramic products with shiny crystal effect on the basis of wear and crack resistance, and has good permeability and three-dimensionality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004964258060000121
    Figure BDA0004964258060000121
  • Figure BDA0004964258060000141
    Figure BDA0004964258060000141
  • Figure BDA0004964258060000151
    Figure BDA0004964258060000151
Patent Text Reader

Abstract

The present invention relates to a preparation process of star crystal glazed ceramics, belonging to the technical field of ceramic processing. The present invention discloses a preparation process of star crystal glazed ceramics, including green embryo molding, base glazing, color design, star crystal glazing, polishing glazing and calcination. When preparing the star crystal glaze, the same components as the base glaze and the polishing glaze are used as the base, and zircon sand particles, nano zirconium oxide, metal oxides and non-ionic surfactants are added. Through the gradient distribution of the particle sizes of different raw material components in the star crystal glaze, the fluidity and uniform dispersion of the glaze are effectively improved, the adhesion and stability between the glazes are enhanced, and high-density ceramics are obtained. While ensuring the wear resistance and crack resistance of the ceramics, the effect of shining crystals is achieved, and good permeability and three-dimensional sense are obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic processing and relates to a preparation process of star crystal glazed ceramics. Background Art

[0002] Natural stone, with its unique colors, textures and various forms of presentation, occupies an important position in the field of modern decoration. The natural characteristics of these stones, such as the natural and smooth texture and rich and diverse colors, give them unique aesthetic value, making them the preferred material for high-end decoration. However, with the continuous increase in the mining activities of natural stones, the exploitable natural mineral resources are gradually decreasing, which has caused considerable pressure on the environment and resources. In this context, various artificial stones have begun to appear in the decoration market and have attracted attention for their sustainability and environmental protection.

[0003] The production of artificial stone not only reduces the industry's dependence on natural mines, but also enables higher controllability and creativity in the design and manufacturing process. As people's living standards continue to improve, consumers' aesthetic needs are also growing, and they are beginning to pursue more refined and high-quality decoration materials. This requires artificial stone to not only imitate the appearance of natural stone, but also to meet higher standards in surface appearance and internal texture. For example, consumers hope that the surface of artificial stone can have a shining crystal effect similar to that of natural stone, so as to create a visual effect like twinkling stars in the night sky in ceramic products.

[0004] In order to meet this market demand, how to ensure the wear resistance and crack resistance of ceramics while producing shiny crystal grain products like natural stone such as crystal sand has become one of the directions pursued by the decorative building materials industry. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation process of star crystal glazed ceramics. Through the gradient distribution of the particle sizes of different raw material components in the star crystal glaze, the adhesion and stability between the glazes are enhanced, while ensuring the wear resistance and crack resistance of the ceramics, the overall gloss of the ceramics is improved, the effect of shining crystals is achieved, and good permeability and three-dimensional sense are possessed.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A preparation process of star crystal glazed ceramics, comprising the following steps: green embryo molding, base glazing, color design, star crystal glazing, polishing glazing, and calcination;

[0008] The star crystal glaze comprises, by percentage, 10-15% zircon sand particles, 10-15% glaze slurry and the remainder of a suspending agent;

[0009] The raw materials of the glaze slurry include, by weight: 9 to 13 parts of nano zirconium oxide, 30 to 50 parts of raw material composition, 8 to 16 parts of metal oxide, 1.5 to 3.5 parts of nonionic surfactant and 35 to 45 parts of water.

[0010] Furthermore, the particle size of the nano zirconium oxide is 50 to 70 nm;

[0011] The raw material composition is composed of kaolin, albite and potassium feldspar in a mass ratio of 1.1-1.5:1.86-2.16:2.04-2.1;

[0012] The metal oxide is composed of titanium dioxide, magnesium oxide and manganese dioxide in a mass ratio of 0.92-1.12:0.76-0.98:1.21-1.45;

[0013] The nonionic surfactant is composed of polyoxyethylene stearate and fatty acid polyoxyethylene ester in a mass ratio of 1.31-1.55:2-2.3;

[0014] The preparation method of the glaze slurry is:

[0015] The ball mill speed is set to 200-300 rpm, the raw material composition is ball-milled through an 80-100 mesh sieve to obtain powder 1, the metal oxide is ball-milled through a 110-120 mesh sieve to obtain powder 2, the nano zirconium oxide, powder 1 and powder 2 are mixed, a non-ionic surfactant and water are added, and the mixture is stirred for 3-4 hours to obtain a glaze slurry.

[0016] Furthermore, the suspending agent is composed of suspending agent A and suspending agent B in a mass ratio of 0.05-0.15:1; the suspending agent A is composed of sodium carboxymethyl cellulose and hydroxyethyl cellulose in a mass ratio of 3.66-3.96:2.4-3.1; the suspending agent B is composed of sodium silicate and sodium phosphate in a mass ratio of 5.7-5.94:7.12-7.4.

[0017] Furthermore, the preparation method of the star crystal glaze is:

[0018] Set the ball mill speed to 180-220 rpm, ball-mill the zircon sand and pass it through a 60-80 mesh sieve, add the obtained zircon sand particles to the glaze slurry, stir at 100-200 rpm for 0.5-1.5 h, add suspending agent A, stir for 1-2 h, increase the speed to 300-400 rpm, add suspending agent B, and stir for 5-6 h to obtain the star crystal glaze.

[0019] Further, the raw materials of the base glaze include, by weight: 15 to 25 parts of nepheline, 20 to 30 parts of albite, 5 to 10 parts of kaolin, 2 to 5 parts of ball clay, 10 to 15 parts of calcined alumina, 15 to 20 parts of quartz, 15 to 25 parts of potassium feldspar, 2 to 4 parts of zinc oxide and 2 to 5 parts of talc;

[0020] The preparation method of the bottom glaze is as follows: weigh the raw materials according to the weight parts, mix and stir them evenly, add water, sodium tripolyphosphate and hydroxyethyl cellulose, start ball milling, sieve and remove iron to obtain the bottom glaze.

[0021] Furthermore, the water, sodium tripolyphosphate and hydroxyethyl cellulose account for 37-43wt%, 0.3-0.4wt% and 0.12-0.18wt% of the base glaze raw material respectively by weight percentage; the ball milling parameters are: ball milling speed is 300-400rmp, and ball milling time is 7.5-8.5h.

[0022] Furthermore, the raw materials for the glaze polishing include, by weight: 20 to 25 parts of albite, 20 to 25 parts of potassium feldspar, 10 to 15 parts of kaolin, 8 to 10 parts of zinc oxide, 10 to 15 parts of dolomite, 15 to 20 parts of low-temperature frit, 10 to 15 parts of wollastonite, 5 to 10 parts of strontium carbonate, and 3 to 5 parts of barium carbonate.

[0023] Furthermore, the low-temperature frit is composed of silicon dioxide, aluminum oxide, calcium oxide, magnesium oxide, potassium oxide, sodium oxide, zinc oxide, and barium oxide in a mass ratio of 54.2-55: 11.85-12.17: 6.7-7: 4.52-4.62: 5.12-5.24: 2-2.16: 6.14-6.32: 8.24-8.5.

[0024] Furthermore, the base glaze glazing process is a pouring glaze process, and the specific parameters are: specific gravity 1.82-1.88g / ml, 300mm*600mm / plate, pouring 75-85g; the star crystal glaze glazing process is a spraying glaze process, and the specific parameters are: specific gravity 1.25-1.35g / ml, 300mm*600mm / plate, spraying 35-45g; the polishing glaze glazing process is a pouring glaze process, and the specific parameters are: specific gravity 1.82-1.86g / ml, 300mm*600mm / plate, pouring 155-165g.

[0025] Furthermore, the calcination parameters are: calcination temperature is 1100-1240° C., and calcination cycle is 40-50 min.

[0026] Beneficial effects of the present invention:

[0027] The star crystal glaze of the present invention is composed of zircon sand particles, glaze slurry and suspending agent, and the glaze slurry includes nano zirconium oxide, raw material composition, metal oxide, non-ionic surfactant and water. The zircon sand particles and nano zirconium oxide in the star crystal glaze are similar in chemical composition. The filling and mixing of the zircon sand particles and nano zirconium oxide due to the difference in particle size helps to enhance the compatibility in the glaze, improve the uniformity of color, and avoid the uneven color caused by the aggregation of zircon sand particles due to the large particle size. In addition, the nano zirconium oxide has a high melting point and chemical stability, which helps to improve the stability of the glaze at high temperature and reduce color changes. The combination of the two can produce a unique starlight effect.

[0028] The suspending agent A in the suspending agent is a high molecular polymer, in which the sodium carboxymethyl cellulose and hydroxyethyl cellulose form a protective layer on the surface of the solid particles due to the entanglement and adsorption of their molecular chains, preventing aggregation between particles and achieving initial dispersion; the sodium silicate in the suspending agent B will form silica colloid after dissolving in water, and sodium phosphate can increase the colloidal properties of the solution. The synergistic use of the two can effectively improve the overall stability and dispersibility of the suspension and further prevent aggregation and sedimentation between particles.

[0029] When star crystal glaze is applied between the base glaze and the polished glaze, the base glaze and the polished glaze are attached to each other with the same raw materials as the star crystal glaze; adding non-ionic surfactants can improve the fluidity, uniformity and stability of the glaze slurry; adding metal oxides can effectively improve thermal stability, reduce thermal stress during sintering, and improve the stability of the glaze structure during calcination. The star crystal glazed ceramics prepared in this way can achieve the effect of shining crystals while ensuring the ceramics are wear-resistant and crack-resistant, and have good permeability and three-dimensional sense. DETAILED DESCRIPTION

[0030] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0031] Example 1

[0032] A preparation process of star crystal glazed ceramics comprises the following steps: green embryo molding, base glazing, color design, star crystal glazing, polishing glazing, and calcination.

[0033] The star crystal glaze of this embodiment includes, by percentage, 10% zircon sand particles, 10% glaze slurry and the balance of suspending agent;

[0034] The raw materials of the glaze slurry of this embodiment include, by weight: 9 parts of nano zirconium oxide, 30 parts of raw material composition, 8 parts of metal oxide, 1.5 parts of non-ionic surfactant and 35 parts of water.

[0035] The particle size of the nano zirconium oxide in this embodiment is 50 nm;

[0036] The raw material composition of this embodiment is composed of kaolin, albite and potassium feldspar in a mass ratio of 1.1:1.86:2.04;

[0037] The metal oxide of this embodiment is composed of titanium dioxide, magnesium oxide, and manganese dioxide in a mass ratio of 0.92:0.76:1.21;

[0038] The nonionic surfactant of this embodiment is composed of polyoxyethylene stearate and fatty acid polyoxyethylene ester in a mass ratio of 1.31:2;

[0039] The preparation method of the glaze slurry of the present embodiment is:

[0040] The ball mill speed was set to 200 rpm, the raw material composition was ball-milled through an 80-mesh sieve to obtain powder 1, the metal oxide was ball-milled through a 110-mesh sieve to obtain powder 2, the nano zirconium oxide, powder 1 and powder 2 were mixed, a non-ionic surfactant and water were added, and the mixture was stirred for 3 hours to obtain a glaze slurry.

[0041] The suspending agent of the present embodiment is composed of suspending agent A and suspending agent B in a mass ratio of 0.05:1; the suspending agent A of the present embodiment is composed of sodium carboxymethyl cellulose and hydroxyethyl cellulose in a mass ratio of 3.66:2.4; the suspending agent B of the present embodiment is composed of sodium silicate and sodium phosphate in a mass ratio of 5.7:7.12.

[0042] The preparation method of the star crystal glaze of this embodiment is:

[0043] The ball mill speed was set to 180 rpm, and the zircon sand was ball-milled and passed through a 60-mesh sieve. The obtained zircon sand particles were added to the glaze slurry, and stirred at 100 rpm for 0.5 h. Suspending agent A was added and stirred for 1 h. After the speed was increased to 300 rpm, suspending agent B was added and stirred for 5 h to obtain the star crystal glaze.

[0044] The raw materials of the base glaze of this embodiment include, by weight: 15 parts of nepheline, 20 parts of albite, 5 parts of kaolin, 2 parts of ball clay, 10 parts of calcined alumina, 15 parts of quartz, 15 parts of potassium feldspar, 2 parts of zinc oxide and 2 parts of talc;

[0045] The preparation method of the bottom glaze of the present embodiment is as follows: weigh the raw materials according to the weight of the present embodiment, mix and stir them evenly, add water, sodium tripolyphosphate and hydroxyethyl cellulose, start ball milling, sieve and remove iron to obtain the bottom glaze.

[0046] In this embodiment, water, sodium tripolyphosphate and hydroxyethyl cellulose account for 37wt%, 0.3wt% and 0.12wt% of the base glaze raw materials of this embodiment respectively by weight percentage; the ball milling parameters of this embodiment are: the ball milling speed is 300rmp, and the ball milling time is 7.5h.

[0047] The raw materials for the glaze polishing of this embodiment include, by weight: 20 parts of albite, 20 parts of potassium feldspar, 10 parts of kaolin, 8 parts of zinc oxide, 10 parts of dolomite, 15 parts of low-temperature frit, 10 parts of wollastonite, 5 parts of strontium carbonate, and 3 parts of barium carbonate.

[0048] The low-temperature frit of this embodiment is composed of silicon dioxide, aluminum oxide, calcium oxide, magnesium oxide, potassium oxide, sodium oxide, zinc oxide, and barium oxide in a mass ratio of 54.2:11.85:6.7:4.52:5.12:2:6.14:8.24.

[0049] The base glaze glazing process of the present embodiment is a pouring glaze process, and the specific parameters are: specific gravity 1.82g / ml, 300mm*600mm / plate, pouring 75g; the star crystal glaze glazing process of the present embodiment is a spraying glaze process, and the specific parameters are: specific gravity 1.25g / ml, 300mm*600mm / plate, spray 35g; the polishing glaze glazing process of the present embodiment is a pouring glaze process, and the specific parameters are: specific gravity 1.82g / ml, 300mm*600mm / plate, pouring 155g.

[0050] The calcination parameters of this embodiment are: calcination temperature is 1100° C., and calcination period is 40 min.

[0051] Example 2

[0052] A preparation process of star crystal glazed ceramics comprises the following steps: green embryo molding, base glazing, color design, star crystal glazing, polishing glazing, and calcination.

[0053] The star crystal glaze of this embodiment includes, by percentage, 15% zircon sand particles, 15% glaze slurry and the balance of suspending agent;

[0054] The raw materials of the glaze slurry of this embodiment include, by weight: 13 parts of nano zirconium oxide, 50 parts of raw material composition, 16 parts of metal oxide, 3.5 parts of non-ionic surfactant and 45 parts of water.

[0055] The particle size of the nano zirconium oxide in this embodiment is 70 nm;

[0056] The raw material composition of this embodiment is composed of kaolin, albite and potassium feldspar in a mass ratio of 1.5:2.16:2.1;

[0057] The metal oxide of this embodiment is composed of titanium dioxide, magnesium oxide, and manganese dioxide in a mass ratio of 1.12:0.98:1.45;

[0058] The nonionic surfactant of this embodiment is composed of polyoxyethylene stearate and fatty acid polyoxyethylene ester in a mass ratio of 1.55:2.3;

[0059] The preparation method of the glaze slurry of the present embodiment is:

[0060] The ball mill speed was set to 300 rpm, the raw material composition was ball-milled through a 100-mesh sieve to obtain powder 1, the metal oxide was ball-milled through a 120-mesh sieve to obtain powder 2, nano zirconium oxide, powder 1 and powder 2 were mixed, non-ionic surfactant and water were added, and the mixture was stirred for 4 hours to obtain a glaze slurry.

[0061] The suspending agent of the present embodiment is composed of suspending agent A and suspending agent B in a mass ratio of 0.15:1; the suspending agent A of the present embodiment is composed of sodium carboxymethyl cellulose and hydroxyethyl cellulose in a mass ratio of 3.96:3.1; the suspending agent B of the present embodiment is composed of sodium silicate and sodium phosphate in a mass ratio of 5.94:7.4.

[0062] The preparation method of the star crystal glaze of this embodiment is:

[0063] The ball mill speed was set to 220 rpm, and the zircon sand was ball-milled and passed through an 80-mesh sieve. The obtained zircon sand particles were added to the glaze slurry, and stirred at 200 rpm for 1.5 h. Suspending agent A was added and stirred for 2 h. After the speed was increased to 400 rpm, suspending agent B was added and stirred for 6 h to obtain the star crystal glaze.

[0064] The raw materials of the base glaze of this embodiment include, by weight: 25 parts of nepheline, 30 parts of albite, 10 parts of kaolin, 5 parts of ball clay, 15 parts of calcined alumina, 20 parts of quartz, 25 parts of potassium feldspar, 4 parts of zinc oxide and 5 parts of talc;

[0065] The preparation method of the bottom glaze of the present embodiment is as follows: weigh the raw materials according to the weight of the present embodiment, mix and stir them evenly, add water, sodium tripolyphosphate and hydroxyethyl cellulose, start ball milling, sieve and remove iron to obtain the bottom glaze.

[0066] In this embodiment, water, sodium tripolyphosphate and hydroxyethyl cellulose account for 43wt%, 0.4wt% and 0.18wt% of the base glaze raw materials of this embodiment respectively by weight percentage; the ball milling parameters of this embodiment are: the ball milling speed is 400rmp, and the ball milling time is 8.5h.

[0067] The raw materials for the glaze polishing of this embodiment include, by weight: 25 parts of albite, 25 parts of potassium feldspar, 15 parts of kaolin, 10 parts of zinc oxide, 15 parts of dolomite, 20 parts of low-temperature frit, 15 parts of wollastonite, 10 parts of strontium carbonate, and 5 parts of barium carbonate.

[0068] The low-temperature frit of this embodiment is composed of silicon dioxide, aluminum oxide, calcium oxide, magnesium oxide, potassium oxide, sodium oxide, zinc oxide, and barium oxide in a mass ratio of 55:12.17:7:4.62:5.24:2.16:6.32:8.5.

[0069] The base glaze glazing process of the present embodiment is a pouring glaze process, and the specific parameters are: specific gravity 1.88g / ml, 300mm*600mm / plate, pouring 85g; the star crystal glaze glazing process of the present embodiment is a spraying glaze process, and the specific parameters are: specific gravity 1.35g / ml, 300mm*600mm / plate, spraying 45g; the polishing glaze glazing process of the present embodiment is a pouring glaze process, and the specific parameters are: specific gravity 1.86g / ml, 300mm*600mm / plate, pouring 165g.

[0070] The calcination parameters of this embodiment are: calcination temperature is 1240° C., and calcination cycle is 50 min.

[0071] Example 3

[0072] A preparation process of star crystal glazed ceramics comprises the following steps: green embryo molding, base glazing, color design, star crystal glazing, polishing glazing, and calcination.

[0073] The star crystal glaze of this embodiment includes, by percentage, 12.5% ​​zircon sand particles, 12.5% ​​glaze slurry and the remainder of suspending agent;

[0074] The raw materials of the glaze slurry of this embodiment include, by weight: 11 parts of nano zirconium oxide, 40 parts of raw material composition, 12 parts of metal oxide, 2.5 parts of non-ionic surfactant and 40 parts of water.

[0075] The particle size of the nano zirconium oxide in this embodiment is 60 nm;

[0076] The raw material composition of this embodiment is composed of kaolin, albite and potassium feldspar in a mass ratio of 1.3:2.01:2.07;

[0077] The metal oxide of this embodiment is composed of titanium dioxide, magnesium oxide, and manganese dioxide in a mass ratio of 1.02:0.87:1.33;

[0078] The nonionic surfactant of this embodiment is composed of polyoxyethylene stearate and fatty acid polyoxyethylene ester in a mass ratio of 1.43:2.15;

[0079] The preparation method of the glaze slurry of the present embodiment is:

[0080] The ball mill speed was set to 250 rpm, the raw material composition was ball-milled through a 90-mesh sieve to obtain powder 1, the metal oxide was ball-milled through a 115-mesh sieve to obtain powder 2, nano zirconium oxide, powder 1 and powder 2 were mixed, non-ionic surfactant and water were added, and the mixture was stirred for 3.5 hours to obtain a glaze slurry.

[0081] The suspending agent of the present embodiment is composed of suspending agent A and suspending agent B in a mass ratio of 0.1:1; the suspending agent A of the present embodiment is composed of sodium carboxymethyl cellulose and hydroxyethyl cellulose in a mass ratio of 3.81:2.75; the suspending agent B of the present embodiment is composed of sodium silicate and sodium phosphate in a mass ratio of 5.82:7.26.

[0082] The preparation method of the star crystal glaze of this embodiment is:

[0083] The ball mill speed was set to 200 rpm, and the zircon sand was ball-milled and passed through a 70-mesh sieve. The obtained zircon sand particles were added to the glaze slurry, and stirred at 150 rpm for 1 h. Suspending agent A was added and stirred for 1.5 h. After the speed was increased to 350 rpm, suspending agent B was added and stirred for 5.5 h to obtain the star crystal glaze.

[0084] The raw materials of the base glaze of this embodiment include, by weight: 20 parts of nepheline, 25 parts of albite, 7.5 parts of kaolin, 3.5 parts of ball clay, 12.5 parts of calcined alumina, 17.5 parts of quartz, 20 parts of potassium feldspar, 3 parts of zinc oxide and 3.5 parts of talc;

[0085] The preparation method of the bottom glaze of the present embodiment is as follows: weigh the raw materials according to the weight of the present embodiment, mix and stir them evenly, add water, sodium tripolyphosphate and hydroxyethyl cellulose, start ball milling, sieve and remove iron to obtain the bottom glaze.

[0086] In this embodiment, water, sodium tripolyphosphate and hydroxyethyl cellulose account for 40wt%, 0.35wt% and 0.15wt% of the base glaze raw material of this embodiment respectively by weight percentage; the ball milling parameters of this embodiment are: the ball milling speed is 350rmp, and the ball milling time is 8h.

[0087] The raw materials for the glaze polishing of this embodiment include, by weight: 22.5 parts of albite, 22.5 parts of potassium feldspar, 12.5 parts of kaolin, 9 parts of zinc oxide, 12.5 parts of dolomite, 17.5 parts of low-temperature frit, 12.5 parts of wollastonite, 7.5 parts of strontium carbonate, and 4 parts of barium carbonate.

[0088] The low-temperature frit of this embodiment is composed of silicon dioxide, aluminum oxide, calcium oxide, magnesium oxide, potassium oxide, sodium oxide, zinc oxide, and barium oxide in a mass ratio of 54.6:12.01:6.85:4.57:5.18:2.08:6.23:8.37.

[0089] The base glaze glazing process of the present embodiment is a pouring glaze process, and the specific parameters are: specific gravity 1.85g / ml, 300mm*600mm / plate, pouring 80g; the star crystal glaze glazing process of the present embodiment is a spraying glaze process, and the specific parameters are: specific gravity 1.3g / ml, 300mm*600mm / plate, spraying 40g; the polishing glaze glazing process of the present embodiment is a pouring glaze process, and the specific parameters are: specific gravity 1.84g / ml, 300mm*600mm / plate, pouring 160g.

[0090] The calcination parameters of this embodiment are: calcination temperature is 1170° C., and calcination cycle is 45 min.

[0091] Comparative Example 1

[0092] On the basis of Example 3, the nano zirconium oxide in the glaze slurry was removed and replaced with zircon sand particles of equal weight. Other conditions were consistent with Example 3.

[0093] Comparative Example 2

[0094] On the basis of Example 3, the nano zirconium oxide in the glaze slurry was removed and replaced with an equal weight of nano zirconium oxide with a particle size of 90 nm. Other conditions were consistent with Example 3.

[0095] Comparative Example 3

[0096] On the basis of Example 3, the raw material composition was removed and replaced with an equal weight of nepheline, and other conditions were consistent with Example 3.

[0097] Comparative Example 4

[0098] On the basis of Example 3, the raw material composition was removed and replaced with an equal weight of dolomite, and other conditions were consistent with Example 3.

[0099] Comparative Example 5

[0100] On the basis of Example 3, the metal oxide was removed and replaced with an equal weight of the raw material composition, and the other conditions were the same as those in Example 3.

[0101] Comparative Example 6

[0102] On the basis of Example 3, the nonionic surfactant was removed and replaced with an equal weight of water, and other conditions were consistent with Example 3.

[0103] Comparative Example 7

[0104] On the basis of Example 3, the method for preparing the glaze slurry was changed as follows: the ball mill speed was set to 250 rpm, the raw material composition, metal oxide, nonionic surfactant and water were stirred and mixed, and ball milled for 3.5 hours to obtain the glaze slurry.

[0105] Comparative Example 8

[0106] On the basis of Example 3, the suspending agent A in the suspending agent was removed and replaced with an equal weight of suspending agent B. Other conditions were the same as those in Example 3.

[0107] Comparative Example 9

[0108] On the basis of Example 3, the sodium carboxymethyl cellulose in the suspending agent A was removed and replaced with an equal weight of hydroxyethyl cellulose, and other conditions were consistent with Example 3.

[0109] Comparative Example 10

[0110] On the basis of Example 3, the suspending agent B in the suspending agent was removed and replaced with an equal weight of suspending agent A, and other conditions were consistent with Example 3.

[0111] Comparative Example 11

[0112] On the basis of Example 3, the sodium silicate in the suspending agent B was removed and replaced with an equal weight of sodium phosphate. Other conditions were the same as those in Example 3.

[0113] 1. Wear resistance test

[0114] The star crystal glazed ceramics prepared in Examples 1 to 3 and Comparative Examples 1 to 11 were used as samples, and the wear resistance of the surface of the star crystal glazed ceramics was measured using the method of GB / T38107-2006. The test results are shown in Table 1.

[0115] Table 1 Wear resistance test results

[0116]

[0117]

[0118] As can be seen from Table 1, the wear resistance level of Examples 1 to 3 is level 5, and the wear resistance level of Comparative Examples 1 to 11 is between levels 2 and 4 due to changes in components or preparation methods. The use of nano zirconium oxide in starlight glaze can reduce the expansion of cracks and increase the density of the material, thereby improving the wear resistance. The use of raw material composition, nonionic surfactant, metal oxide and suspending agent is also to improve the mutual dependence between raw materials, prevent aggregation and sedimentation between particles, thereby achieving uniform and stable distribution of glaze and improving wear resistance.

[0119] 2. Crack resistance test

[0120] The star crystal glazed ceramics prepared in Examples 1 to 3 and Comparative Examples 1 to 11 were used as samples, and the crack resistance of the star crystal glazed ceramics was tested using the method of GB / T34252-2017. The test results are shown in Table 2.

[0121] Table 2 Crack resistance test results

[0122] Crack resistance index / h Example 1 23.9 Example 2 24.2 Example 3 24.7 Comparative Example 1 16.1 Comparative Example 2 16.8 Comparative Example 3 13.5 Comparative Example 4 13.7 Comparative Example 5 15.5 Comparative Example 6 14.1 Comparative Example 7 12.9 Comparative Example 8 15.3 Comparative Example 9 13.2 Comparative Example 10 10.8 Comparative Example 11 11.2

[0123] It can be seen from Table 2 that the star crystal glazed ceramics prepared in Examples 1 to 3 have good crack resistance, while Comparative Examples 1 to 11 are prepared on the basis of Example 3. Any change in the components, combination or preparation method will result in a significant decrease in the crack resistance of the prepared ceramics.

[0124] 3. Appearance evaluation of Star Glazed Ceramics

[0125] The star crystal glazed ceramics prepared in Examples 1 to 3 and Comparative Examples 1 to 11 were used as samples, and the uniformity of the star crystal distribution, the color and gloss of the star crystals, and the overall aesthetics of the star crystal effect were evaluated. The evaluation results are shown in Table 3.

[0126] The assessment levels are as follows:

[0127] The evaluation of "uniformity of star crystal distribution" is divided into 4 levels: Level 1 is extremely uneven distribution of star crystals, with large areas of aggregation or blank areas; Level 2 is not very uniform distribution of star crystals, with small areas of aggregation or blank areas; Level 3 is relatively uniform distribution of star crystals, with only a few aggregations or blank areas; Level 4 is very uniform distribution of star crystals, with no obvious aggregation or blank areas;

[0128] The evaluation of "color and gloss of star crystals" is divided into 4 levels: Level 1 is dull color and poor gloss of star crystals, Level 2 is average color and fair gloss of star crystals, Level 3 is bright color and good gloss of star crystals, and Level 4 is very bright color and excellent gloss of star crystals;

[0129] The evaluation of "the overall aesthetics of the star crystal effect" is divided into 4 levels: Level 1 is poor overall effect and lack of aesthetics, Level 2 is average overall effect and fair aesthetics, Level 3 is good overall effect and good aesthetics, and Level 4 is excellent overall effect and high aesthetics.

[0130] Table 3 Appearance evaluation results of star crystal glazed ceramics

[0131]

[0132]

[0133] From the appearance evaluation results of the star crystal glazed ceramics in Table 3, it can be seen that the star crystal glazed ceramics prepared in Examples 1 to 3 have very uniform star crystal distribution, no obvious aggregation or blank areas, very bright star crystal color, excellent gloss, and excellent overall effect, with high aesthetics, good permeability and three-dimensional sense, while Comparative Examples 1 to 11 are prepared on the basis of Example 3, and arbitrarily change the components or combinations or preparation methods therein, and the star crystal glazed ceramics obtained have significantly reduced star crystal distribution, star crystal color and gloss, and overall star crystal effect, and cannot achieve the expected shiny crystal effect.

[0134] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A process for preparing star crystal glazed ceramics, characterized in that: The following steps are involved: Green embryo molding, base glazing, color design, star crystal glazing, polishing glazing, calcination; The star crystal glaze comprises, by percentage, 10-15% zircon sand particles, 10-15% glaze slurry and the remainder of a suspending agent; The raw materials of the glaze slurry include, by weight: 9 to 13 parts of nano zirconium oxide, 30 to 50 parts of raw material composition, 8 to 16 parts of metal oxide, 1.5 to 3.5 parts of nonionic surfactant and 35 to 45 parts of water; The particle size of the nano zirconium oxide is 50-70 nm; The raw material composition is composed of kaolin, albite and potassium feldspar in a mass ratio of 1.1-1.5:1.86-2.16:2.04-2.1; The metal oxide is composed of titanium dioxide, magnesium oxide and manganese dioxide in a mass ratio of 0.92-1.12:0.76-0.98:1.21-1.45; The nonionic surfactant is composed of polyoxyethylene stearate and fatty acid polyoxyethylene ester in a mass ratio of 1.31-1.55:2-2.3; The preparation method of the glaze slurry is: The ball mill speed is set to 200-300 rpm, the raw material composition is ball-milled through an 80-100 mesh sieve to obtain powder 1, the metal oxide is ball-milled through a 110-120 mesh sieve to obtain powder 2, the nano zirconium oxide, powder 1 and powder 2 are mixed, a nonionic surfactant and water are added, and the mixture is stirred for 3-4 hours to obtain a glaze slurry; The suspending agent is composed of suspending agent A and suspending agent B in a mass ratio of 0.05-0.15:1; the suspending agent A is composed of sodium carboxymethyl cellulose and hydroxyethyl cellulose in a mass ratio of 3.66-3.96:2.4-3.1; and the suspending agent B is composed of sodium silicate and sodium phosphate in a mass ratio of 5.7-5.94:7.12-7.

4.

2. The process for preparing star crystal glazed ceramics according to claim 1, characterized in that: The preparation method of the star crystal glaze is: Set the ball mill speed to 180~220rmp, ball-mill the zircon sand and pass it through a 60~80 mesh sieve, add the obtained zircon sand particles to the glaze slurry, stir at 100~200rmp for 0.5~1.5h, add suspending agent A, stir for 1~2h, increase the speed to 300~400rmp, add suspending agent B, and stir for 5~6h to obtain star crystal glaze.

3. The process for preparing star crystal glazed ceramics according to claim 1, characterized in that: The raw materials of the base glaze include, by weight: 15-25 parts of nepheline, 20-30 parts of albite, 5-10 parts of kaolin, 2-5 parts of ball clay, 10-15 parts of calcined alumina, 15-20 parts of quartz, 15-25 parts of potassium feldspar, 2-4 parts of zinc oxide and 2-5 parts of talc; The preparation method of the bottom glaze is as follows: weigh the raw materials according to the weight parts, mix and stir them evenly, add water, sodium tripolyphosphate and hydroxyethyl cellulose, start ball milling, sieve and remove iron to obtain the bottom glaze.

4. The process for preparing star crystal glazed ceramics according to claim 3, characterized in that: The water, sodium tripolyphosphate and hydroxyethyl cellulose account for 37-43wt%, 0.3-0.4wt% and 0.12-0.18wt% of the base glaze raw material respectively by weight percentage; the ball milling parameters are: the ball milling speed is 300-400rmp, and the ball milling time is 7.5-8.5h.

5. The process for preparing star crystal glazed ceramics according to claim 1, characterized in that: The raw materials for the glaze polishing include, by weight: 20-25 parts of albite, 20-25 parts of potassium feldspar, 10-15 parts of kaolin, 8-10 parts of zinc oxide, 10-15 parts of dolomite, 15-20 parts of low-temperature frit, 10-15 parts of wollastonite, 5-10 parts of strontium carbonate, and 3-5 parts of barium carbonate.

6. The process for preparing star crystal glazed ceramics according to claim 5, characterized in that: The low-temperature frit is composed of silicon dioxide, aluminum oxide, calcium oxide, magnesium oxide, potassium oxide, sodium oxide, zinc oxide and barium oxide in a mass ratio of 54.2-55: 11.85-12.17: 6.7-7: 4.52-4.62: 5.12-5.24: 2-2.16: 6.14-6.32: 8.24-8.

5.

7. The process for preparing star crystal glazed ceramics according to claim 1, characterized in that: The bottom glaze glazing process is a pouring glaze process, and the specific parameters are: specific gravity 1.82~1.88g / ml, 300mm*600mm / plate, pouring 75~85g; the star crystal glaze glazing process is a spraying glaze process, and the specific parameters are: specific gravity 1.25~1.35g / ml, 300mm*600mm / plate, spraying 35~45g; the polishing glaze glazing process is a pouring glaze process, and the specific parameters are: specific gravity 1.82~1.86g / ml, 300mm*600mm / plate, pouring 155~165g.

8. The process for preparing star crystal glazed ceramics according to claim 1, characterized in that: The calcination parameters are as follows: calcination temperature is 1100-1240° C., and calcination cycle is 40-50 min.

Citation Information

Patent Citations

  • Wear-resistant antifouling ceramic starlight glazed brick and preparation method thereof

    CN112979349A

  • Nano soft-light super wear-resistant diamond glaze, ceramic tile and preparation method of nano soft-light super wear-resistant diamond glaze

    CN114772933A

  • Star blazed flash rock plate and preparation method thereof

    CN117510238A